Projection Analysis of Economic Development in Indonesia in the Perspective of Islamic Economy Using the Vecm Model - Raseuky, Maulidina; Harahap, Isnaini; Arif Lubis, Fauzi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The purpose of this research is to analyze how inflation, unemployment, and government expenditure affect economic growth in Indonesia in the 2000-2022 period. To project the economy in Indonesia in the short term (next 10 years) and in the long term (next 20 years). This type of research uses quantitative methods. The data used are secondary data sourced from the official website of SEKI-BI, the Central Bureau of Statistics, the World Bank, and SIMREG (Regional Basic Data Management and Information System) from 1990 to 2022 so that the number of samples in this study was 128 samples using a purposive sampling technique to determine information. While technical data analysis uses Vector Autoregressive Analysis (VAR) and Vector Error Correction Model (VECM). Based on the results of the Impulse Response Function, we can see that the shock resulted from the previous period's GDP, the GDP Deflator, TPT and GE were very volatile and unstable in the short term, the biggest shock was found in the early period of year 1 to year 20, then the shock subsides from the mid to late period (25th year to 50th year), in the final period the shocks are still starting to stabilize.